Role of ultrasonication duration and surfactant on characteristics of ZnO and CuO nanofluids - Afzal, Asif; Khan, Sher Afghan; Saleel, Ahmed (IOP Publishing, 2019)
Ultrasonication duration during the preparation of nanofluids has an important role on its various characteristics. Recently, the role of the surfactant is also found to be particularly significant in the properties of nanofluids. The role of ultrasonication duration and surfactant is together studied in this article on ZnO and CuO nanofluid. After the number of experiments with different surfactants, stable ZnO nanofluid is prepared using both EBT (monochrome black T) and OA(allylamine) surfactant while CuO is prepared using alone as it can be easily stabilized. Ultrasonication time is increased from 2 h to 8 h and different properties are analyzed in detail. Zeta potential, UV-vis analysis, pH value, specific heat capacity, specific gravity, viscosity, and thermal conductivity are analyzed for the three nanofluids. Stability of ZnO+EBT nanofluid is found to be excellent than the ZnO+OAand CuO+OAnanofluid. pH value, specific heat capacity, and specific gravity remained unaltered with an increase in ultrasonication time while the remaining properties changed considerably.